Systematic review: effect of lipid and lipoprotein profiles on atherosclerosis and cardiovascular disease risk in premenopausal and postmenopausal women - Avinash Namdeo Jadhao; Anita Shivaji Chalak; Sandip Deepak Lambe (Advances in Medical, Pharmaceutical and Dental Research)
Understanding the relationship between lipid profiles and cardiovascular health is crucial, particularly in the context of atherosclerosis, a major cause of cardiovascular diseases. Dyslipidemia, characterized by high LDL cholesterol and triglycerides and low HDL cholesterol, is a significant contributor to atherosclerosis. In women, menopause shifts the lipid profile from a protective to an atherogenic one due to reduced estrogen levels, increasing cardiovascular risk. Additionally, surgical procedures like hysterectomy with or without oophorectomy, which cause abrupt declines in estrogen, further disrupt lipid profiles. Among 243 initially identified publications, 15 were thoroughly reviewed, leading to the inclusion of 9 studies. These studies show that surgical menopause typically results in increased total cholesterol, LDL-C, and triglycerides, and decreased HDL-C, heightening cardiovascular risk. Effective monitoring and management of lipid profiles post-surgery are essential, and ovarian conservation during hysterectomy may mitigate some adverse lipid effects. Further longitudinal studies and personalized interventions are needed to enhance cardiovascular health in women undergoing surgical menopause.   Received: 17 July 2024 Accepted: 21 August 2024 Published: 09 September 2024